Morphology and electron circulation of ZTO (zinc tin oxide) on SLG for CZTS thin film solar cell - Kang, Jian Xian; Abdullah, Huda; Yuliarto, Brian; Md Akhtaruzzaman; Othman, Mohd Hafiz Dzarfan; Yap, Wing Fen; Mohamad, Md Fauzi (IEEE, 2022)
Among the 3rd generation of photovoltaics (PVs), Cu2ZnSnS4 (CZTS), having the kesterite structure, was one of the most promising absorber layer candidates for low-cost thin-film solar cells. Also, it was composed of earth affluent and non-toxic elements, promising price reductions in prospect compared to CIGS solar cell. However, the common buffer layer for CZTS is Cadmium Sulphate (CdS). The CdS could be replace by a better material, Zinc Tin Oxide. On the other hand, ZnSnO 3 (ZTO) with several advantages, and the high field-effect electron mobility of ZTO with as high as 20–50 cm2/V s. The master plan was scrutinized opportunity to supersede the default CZTS buffer layer Cadmium Sulphate with Zinc Tin Oxide. In this research, the ZTO layer was deposited on top of the soda-lime glass (SLG). The Zinc Tin Oxide was deposited on top SLG through solution process method. The deposition was tested to show ZTO behavior changes on these layers. Morphological show more tin doped results in bigger grain size. The direct optical band gap of ZTO was calculated to be 2.7 - 3.02 eV.The Zn 0.867 Sn 0.133 OCδ shows conductivity of 26µA at 2V.).